Willingness to pay for accessible elderly housing in Korea - Lee, So Young; Yoo, Sung Eun (International Journal of Strategic Property Management, 2020)
The demands and requirements for accessible housing of a diverse population can vary considerably, especially considering that “aging in place” is a growing trend among the elderly. In an aging society, accessibility can be a housingmarket commodity, and the demand in Korea for this commodity is expected to increase. The purpose of this study is to investigate the value of accessible housing and the consumer᾽s willingness to pay (WTP) using the Contingent Valuation Method (CVM). For the analysis, 700 people were interviewed based on the housing type and age group. More than half of the respondents were willing to pay more for accessible housing compared to conventional housing. The WTP amount differed considerably with the age group, gender, housing type, size of unit, and tenure type. The elderly showed a greater WTP than the younger group; higher economic status (as indicated by monthly household income), educational level, and home ownership influenced WTP. The results showed that accessible housing could be an important housing choice for the elderly and can be adopted as an affordable option. Moreover, the results can help reduce the negative perception of accessible housing, which is commonly associated with its supposed high costs.First published online 16 October 2019